2021
DOI: 10.1038/s41598-021-85775-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treated HIV infection is associated with platelet mitochondrial dysfunction

Abstract: HIV infection and antiretroviral therapy have been linked to mitochondrial dysfunction. The role of platelet mitochondrial dysfunction in thrombosis, immunoregulation and age-related diseases is increasingly appreciated. Here, we studied platelet mitochondrial DNA content (mtDNApl) and mitochondrial function in people living with HIV (PLHIV) and related this to platelet function. In a cohort of 208 treated PLHIV and 56 uninfected controls, mtDNApl was quantified, as well as platelet activation, platelet agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
0
10
1
Order By: Relevance
“…The study found a significant reduction in the mean mtDNA copies/cells in the ART pregnancy group compared to the control group (p < 0.001). Comparison of mean mtDNA copies in ART-exposed pregnancies did not show significant differences in the first, second, or third trimesters [12].…”
Section: Discussionmentioning
confidence: 72%
“…The study found a significant reduction in the mean mtDNA copies/cells in the ART pregnancy group compared to the control group (p < 0.001). Comparison of mean mtDNA copies in ART-exposed pregnancies did not show significant differences in the first, second, or third trimesters [12].…”
Section: Discussionmentioning
confidence: 72%
“…infected controls [83]. The implications of mitochondrial density in PMVs is unknown; however, long-term treated HIV is associated with reduced platelet mitochondrial content, supporting the presence of MVs with lowered mitochondrial densities [88]. Circulating MVs, most of which are platelet-derived, were also implicated in adversely affecting endothelial cells in an in vitro model [87].…”
Section: The Role Of Pmvs In Viral Infectionsmentioning
confidence: 94%
“…Characterization of circulating microvesicles through flow cytometry indicates that most of circulating MVs are PMVs (79%) in HIV infection and that these MVs have significantly lowered mitochondrial densities compared to uninfected controls [83]. The implications of mitochondrial density in PMVs is unknown; however, long-term treated HIV is associated with reduced platelet mitochondrial content, supporting the presence of MVs with lowered mitochondrial densities [88]. Circulating MVs, most of which are platelet-derived, were also implicated in adversely affecting endothelial cells in an in vitro model [87].…”
Section: The Role Of Pmvs In Viral Infectionsmentioning
confidence: 97%
“…RANTES, a CCR5 ligand, was determined in PLHIV only by ELISA (R and D systems, Minneapolis, USA) in citrated plasma samples according to the manufacturer’s instructions 32 .…”
Section: Methodsmentioning
confidence: 99%